1983
DOI: 10.1055/s-2007-1018685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermittent Hypoxia on Intravenous Glucose Tolerance and Insulin Sensitivity in Anaesthetized Normal Rats

Abstract: The effect of intermittent tissue hypoxia on glucose tolerance and insulin sensitivity was investigated in normal rats. Intermittent hypoxia of 10% 0 2 atmosphere for three hours per day for three weeks led to increased serum insulin levels following an intravenous glucose load without any alteration of glucose tolerance (1 g glucose per kg body weight). These data do not support the hypothesis that the beneficial effect of physical training on glucose tolerance as demonstrated in normal and fatty ZUCKER rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Animal studies also have shown that insulin resistance may be induced or exacerbated by overnight sympathoexcitation and/or hypoxemia. 9 Several clinic-based studies have demonstrated a relationship between SDB and insulin resistance. 15,22,[44][45][46][47][48] In one case-control study, HOMA-IR was significantly higher in a sleep apnea sample than a BMI-matched control group.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies also have shown that insulin resistance may be induced or exacerbated by overnight sympathoexcitation and/or hypoxemia. 9 Several clinic-based studies have demonstrated a relationship between SDB and insulin resistance. 15,22,[44][45][46][47][48] In one case-control study, HOMA-IR was significantly higher in a sleep apnea sample than a BMI-matched control group.…”
Section: Discussionmentioning
confidence: 99%
“…Among the diabetic patients described here, two presented initially with nonarteritic anterior ischemic optic neuropathy. Djovkar et al [34] also showed influence of intermittent hypoxia on intravenous glucose tolerance and insulin sensitivity in anaesthetized normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental protocols expose rodents to intermittent hypoxia (IH 1 ) to simulate the blood gas changes that occur in sleep apnea; while they vary in cycle length, severity of hypoxia, number of hypoxic episodes per hour, and number of exposure days, they are quite consistent in reporting mild hypertension (Fletcher 2001; Kanagy et al 2001; Lesske et al 1997), augmented vascular contractility (Allahdadi et al 2005; Julien et al 2003; Tahawi et al 2001), and metabolic alterations (Djovkar 1983; Holm et al 1973; McNulty et al 1996; Polotsky et al 2003). Thus, despite slightly different results in the time to onset of cardiovascular changes and the degree of resulting pathology, the similarities are more striking than the differences.…”
Section: Rodent Models Of Intermittent Hypoxiamentioning
confidence: 99%